2017
DOI: 10.1186/s12866-017-0988-4
|View full text |Cite
|
Sign up to set email alerts
|

Purification, characterization and amino acid content of cholesterol oxidase produced by Streptomyces aegyptia NEAE 102

Abstract: BackgroundThere is an increasing demand on cholesterol oxidase for its various industrial and clinical applications. The current research was focused on extracellular cholesterol oxidase production under submerged fermentation by a local isolate previously identified as Streptomyces aegyptia NEAE 102. The crude enzyme extract was purified by two purification steps, protein precipitation using ammonium sulfate followed by ion exchange chromatography using DEAE Sepharose CL-6B. The kinetic parameters of purified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…The activity of cholesterol oxidase (Cho) from the HGMS2 strain was spectrophotometrically determined by monitoring the generation of hydrogen peroxide during the cholesterol oxidation reaction according to the method of El-Naggar et al [40]. In principle, to measure the enzyme activity, a horseradish peroxidase-coupled reaction was used to catalyze the conversion of hydrogen peroxide to oxygen to oxidize 4-aminoantipyrine and phenol and produce the dye quinoneimine, which exhibits maximum absorption at 500 nm.…”
Section: Cholesterol Oxidase Activity Assaymentioning
confidence: 99%
“…The activity of cholesterol oxidase (Cho) from the HGMS2 strain was spectrophotometrically determined by monitoring the generation of hydrogen peroxide during the cholesterol oxidation reaction according to the method of El-Naggar et al [40]. In principle, to measure the enzyme activity, a horseradish peroxidase-coupled reaction was used to catalyze the conversion of hydrogen peroxide to oxygen to oxidize 4-aminoantipyrine and phenol and produce the dye quinoneimine, which exhibits maximum absorption at 500 nm.…”
Section: Cholesterol Oxidase Activity Assaymentioning
confidence: 99%
“… 4 , Brevibacterium sterolicum 5 , Mycobacterium sp. 6 , Streptomyces violascens 7 , Streptomyces cavourensis 8 , Streptomyces aegyptia 9 , etc. COD produced from the microbes is of great commercial interest and widely used for the determination of cholesterol concentration in serum and food samples 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Central composite design (CCD) is used to study the interaction effect of the factors significantly affecting the product formation. Similarly, Response surface methodology (RSM) is used to describe the behavior of the response in the selected design space 8 , 20 . Whereas, Genetic algorithm (GA) approach is used for solving both constrained and unconstrained optimization problems based on natural selection.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the nitrogen sources used during fermentation has an impact on L-asparaginase production [1,2,19]. El-naggar et al [25] suggested that Lasparaginase activity increases with the concentration of L-asparagine in the medium. In the present study, we found that L-asparagine and malt extract stimulated L-asparaginase activity more than using one nitrogen source alone.…”
Section: Discussionmentioning
confidence: 99%